Surgical Management of Canine Prostatic Neoplasia: - A Case Report - V. Bhuvaneshwari,; D. Jenita Rani,; M. Madeena Begum, (The Indian Veterinary Journal, 2023)
Aneleven year old castratedmale Labrador retriever dog was brought to the hospital, with a history of recurrent urinary incontinence. Physical examination revealed no gross abnormalities. However, urinary catheter was not able to reach the bladder while trying for retrograde urinary catheterization. Rectal examination revealed, enlarged prostate. Abdominal radiography confirmed the case as prostate enlargement. Pre-operative blood collected for hemato-biochemical analysis and thoracic radiograph was taken to rule out metastasis. Total prostatectomy was performed under general anaesthesia and bladder neck was reconstructed with pelvic urethra. Histopathological analysis of the excised Prostate gland mass was, confirmed as the prostateneoplasia. Post-operativelyurinary bladder catheter was fixed,systemic antibiotic and supportive therapy along with surgical wound dressing was continued for seven days. Urinary Catheter was removed on fifth post-operative day. The sutures were removed on 7th post-operative day after the complete healing and the animal made an uneventful recovery.